The Economy of Immigrants: The Case of the Netherlands - Gençosmanoğlu , Ömer Tarık (Academician Publishing Book DOI Portal, 2023)
This book examines the impact of immigrant groups on the economy in the Netherlands. Based on comprehensive data obtained through research conducted at Erasmus University, the author explores the relationship between international trade and migration. The book focuses on the participation of immigrants in the national labor market, income distribution, economy (both in terms of companies and self-employed entrepreneurs), and foreign trade in the Netherlands. The author analyzes different immigrant groups in comparison to each other and the native population. The significant immigrant population in the Netherlands allows for this study to be conducted. The book will be an important resource for economists, political scientists, sociologists, and policymakers. Additionally, immigrants and non-governmental organizations interested in understanding the socio-economic differences among immigrant groups and their relationships with the native population will also find it relevant.